The Effects of CT on Blood Components for Diabetic Patients - Farah HASAN; Aedah AL-KAISY; Mohamed HASAN (Modern Medicine)
Objectives: Computed tomography CT scan is a medical device used in diagnosis; however, the radiation of CT will affect the human body such as blood components. Materials and Methods: In this study, the blood component of diabetic patients will examine the effect of CT radiation on blood components by withdrawing samples of 2 cc from diabetes patients’ blood before and after a CT scan on the body for patients who are exposed to the head, chest, and abdomen. Results: There were no significant statistical differences were between blood counts (WBC, RBC, and Hg) before and after the CT scan for the head, chest, and abdomen. Conclusions: The main conclusion of the current study is that, depending on the results, the CT scan is safe for patients.